Dampak Kecerdasan Buatan (AI) terhadap Pola Pikir Cerdas Mahasiswa di Pontianak - Faisal, Muhammad (NUCLEUS, 2024)
This research examines the impact of artificial intelligence (AI) on the growth mindset of students in Pontianak. AI has become a revolutionary technology applied in education, such as adaptive learning systems, virtual assistants, and automated assessment tools that provide real-time feedback. The use of AI has the potential to enhance critical and analytical thinking skills, as well as encourage students to develop a more open and adaptive mindset. However, this research also found that excessive reliance on AI can hinder the development of deep thinking and creativity among students, with a tendency to seek quick solutions instead of engaging in exploratory thinking. Through a mixed-methods approach that combines quantitative and qualitative methods, this research identifies the positive and negative impacts of AI on students' mindsets. Quantitative analysis shows that the use of AI enhances thinking flexibility, while qualitative interviews indicate a potential decrease in motivation for independent thinking due to technology dependence. This research offers strategic recommendations for the wise use of AI in education, in order to maximize its benefits without diminishing students' cognitive abilities.